Creating a cross-disciplinary hub for active student learning in the library: The card game - Key, Newton; Newell, Zachary (Septentrio Conference Series, 2020)
Two recent technology-driven tendencies in library-faculty collaboration – (1) embedding librarians in the online components of courses, and (2) repurposing certain library spaces to become makerspaces – often embrace the learning strategy of focusing on students as creators. Booth Library at Eastern Illinois University, in collaboration with a faculty-led Faculty Development office and a Humanities Center, has advanced both the leveraging of technology in learning and the creation of a library makerspace, and added a third component, (3) placing an active learning classroom (ALC) connected to a design lab as the first stage of a Center for Student Innovation (CSI). This process, grounded in research on learning spaces and universal design, had led us to ask: what space best encourages creativity in the learning process? We propose to showcase a “think-pair-share” card game to demonstrate how we are re-centering the library as a center for knowledge creation, and a space for promoting discovery, in a format that invites Creating Knowledge participants to fine-tune our model or advance alternatives. That is, the library is building collaborations for re-thinking space, and re-positioning the library as central to teaching and learning, to foster 21st century skills around information, communication, and ethical/social impact. The card game will demonstrate ways to help students and faculty to create knowledge, and how information as a product is modeled, remodeled and reinterpreted for pedagogically creative teaching and learning. The implementation of the CSI has stimulated larger discussions in the library and across campus about the role of a “future-present” library. How can faculty and students embrace discovery as a means rather than an end? What role does the library play in facilitating teaching and learning? What does the future library look like? The presentation and card game will answer these questions through audience feedback and participation.